Caracterización de dos experiencias exitosas de negocios inclusivos en Colombia. (2015)
The case report presented here reviews two experiences of successful inclusive business, which allow to highlight new trends in corporate social responsibility and its forms of hybridizing with other scientific fields such as the common good economy and corporate resilience. The methodology involved using qualitative and quantitative tools based on virtual ethnography to understand the peculiarities of two firms that make a difference in the way of doing business.